2015
DOI: 10.1007/s10953-015-0339-8
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Phloroglucinol Tris(cyclic 2,2-dimethyl-1,3-propanediol phosphate) in Different Solvents

Abstract: The solubility of phloroglucinol tris(cyclic 2,2-dimethyl-1,3-propanediol phosphate) in methanol, ethanol, acetone, tetrahydrofuran, acetonitrile, 1,4-dioxane, chloroform and dichloromethane was measured by a static analytic method over the temperature range from 288 to 318 K. The modified Apelblat equation and the Buchowski-Ksiazaczak (kh) equation were applied to represent the measurement results. The results show that the two models can satisfactorily reproduce the experimental data. The thermodynamic prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Phloroglucinol including other polyphenol derivatives contained in brown alga have solubility in methanol, ethanol, acetone, tetrahydrofuran, acetonitrile, 1,4-dioxane, chloroform and dichloromethane. 14 Based on the result of this study, E50 showed the highest total phenolic content (27.63±1.05 mg PGE/g extract) than E30 and E70. In the study from Chakraborty (2013) showed total phenolic content of methanol extract of T. conoides was 16.64±0.10 mg GAE/g extract.…”
Section: Acknowledgementmentioning
confidence: 69%
“…Phloroglucinol including other polyphenol derivatives contained in brown alga have solubility in methanol, ethanol, acetone, tetrahydrofuran, acetonitrile, 1,4-dioxane, chloroform and dichloromethane. 14 Based on the result of this study, E50 showed the highest total phenolic content (27.63±1.05 mg PGE/g extract) than E30 and E70. In the study from Chakraborty (2013) showed total phenolic content of methanol extract of T. conoides was 16.64±0.10 mg GAE/g extract.…”
Section: Acknowledgementmentioning
confidence: 69%